Propuesta de Mejora en los Procesos de Servicios de Motocicletas Motopits a Partir de la Filosofía Lean Manufacturing (2022)
This research is based on the principles of the Lean Manufacturing philosophy, aimed at improving the motorcycle assistance processes in the Motopits company, where the support of the collaborators who allowed the fulfillment of the objectives was taken into account. This case study exposes the implementation of the Lean Manufacturing philosophy according to the processes and deficiencies of the organization that was carried out through three stages, initially the state of the motorcycle technical assistance service processes was diagnosed where failures were evidenced in the development of activities due to the absence of a culture of order and cleanliness, constant shutdowns due to the lack of control and maintenance of equipment, deficiencies in the administration of information and lack of standardization of processes and procedures. From the diagnosis, the tools that could be applied were analyzed so that they were suitable as an improvement proposal that would show greater optimization of the Motopits company processes, which were socialized and approved by the organization for their respective implementation.